Oxford atlas project for Pakistan - Oxford University Press (Karachi: Oxford University Press., 2024)
The Oxford Atlas Project for Pakistan, Fourth Edition, authored by Oxford University Press, is an educational atlas tailored for students in Pakistan. It offers a wide array of maps and geographic information, with a primary focus on Pakistan's physical, political, and socio-economic landscapes. The atlas features thematic maps highlighting key topics such as climate, population distribution, agriculture, industry, and natural resources. In addition, it situates Pakistan within a global context through comprehensive world maps. Designed to support the geography curriculum, the atlas helps students develop essential skills in map reading and spatial analysis.